Inspecting the Dangers of Feeling like a Fake: An Empirical Investigation of the Impostor Phenomenon in the World of Work - Neureiter, Mirjam; Traut-Mattausch, Eva (Frontiers in Psychology, 2016)
To investigate the link between the impostor phenomenon (IP), career self-management (CSM) factors, and work-relevant outcomes, we looked at the IP's impact on career optimism, career adaptability, and knowledge of the job market, as well as on employee- and organizationally-relevant outcomes. We analyzed data from 238 working professionals (57% female) using parallel multiple mediation analyses. The results revealed that the IP was negatively related to all work-relevant outcomes through decreased CSM factors, which were subsequently associated with the outcomes. As hypothesized, employee-relevant subjective outcomes were mediated by optimism and employee-relevant objective (i.e., economic) outcomes by adaptability and knowledge. Additional mediating effects occurred. Regarding organizationally relevant outcomes, adaptability mediated the IP's impact on organizational citizenship behavior. The IP was only indirectly related to continuance commitment through adaptability and to affective commitment through optimism. We discuss the theoretical and practical implications and offer ideas for future research.